Single-cell transcriptomics following ischemic injury identifies a role for B2M in cardiac repair - Bas Molenaar (Nature Portfolio, 2021)
Molenaar et al. use scRNA-seq to profile cardiac cell gene expression changes at three time points following ischemic injury. They observe that B2M is secreted by cardiomyocytes following injury, promoting scar formation. This data may be useful in finding therapeutic targets for cardiac repair